2020
DOI: 10.1163/15685411-00003302
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of the root-lesion nematode, Pratylenchus zeae, on rice genotypes under different hydro-ecologies in Tanzania

Abstract: Summary The root-lesion nematode, Pratylenchus zeae, is commonly found in upland rice fields. To measure the impact of the nematode on rice production, a screenhouse experiment was conducted using two farmer-adapted Oryza sativa cultivars, ‘Supa’ (‘SurinamV-880’) and ‘SARO-5’ (‘TXD 306’), under flooded, upland and drought water regimes imposed at 7 days post-inoculation of mixed-stage nematodes (200, 500, 1000, 3000 and 10 000 plant−1). Growth and yield parameters were recorded, and the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The results of our pot experiment were consistent with those of the paddy field investigation, both of which prove that field water is closely related to the reproduction of nematodes and that low soil moisture is conducive to the reproduction of nematodes. The importance of the water regime to nematodes has also been illustrated in several other reports ( Cabasan et al, 2017 ; Nzogela et al, 2019 ; Soriano et al, 2000 ; Win et al, 2013 ). Previous studies have reported that nematodes of M. graminicola lay eggs inside the root cortex, and hatched J2 can be released into the soil or remain within the gall to migrate and reinfect the same or adjacent roots by establishing new feeding sites ( Mattos et al, 2019 ; Kyndt et al, 2012 ; Rao and Israel, 1973 ).…”
Section: Discussionsupporting
confidence: 56%
“…The results of our pot experiment were consistent with those of the paddy field investigation, both of which prove that field water is closely related to the reproduction of nematodes and that low soil moisture is conducive to the reproduction of nematodes. The importance of the water regime to nematodes has also been illustrated in several other reports ( Cabasan et al, 2017 ; Nzogela et al, 2019 ; Soriano et al, 2000 ; Win et al, 2013 ). Previous studies have reported that nematodes of M. graminicola lay eggs inside the root cortex, and hatched J2 can be released into the soil or remain within the gall to migrate and reinfect the same or adjacent roots by establishing new feeding sites ( Mattos et al, 2019 ; Kyndt et al, 2012 ; Rao and Israel, 1973 ).…”
Section: Discussionsupporting
confidence: 56%
“…Soil nematodes are semiaquatic animals that rely on water films or water-filled soil pores for movement; hence, changes in water availability are likely to affect their activity in the short term and nematode abundances and community composition in the longer term (Nzogela et al, 2020). A recent global survey of nematode trophic groups showed that nematode abundances are positively correlated with mean annual precipitation, at least when other factors, such as soil carbon (C) and nutrients, are not limiting abundances (van den Hoogen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The results from this research could have implications for nematode management because both crops are common in Guanacaste. Therefore, the presence of this crops permits the reproduction and survival of the nematode species and might reduce the positive impact of the sugar cane/rice rotation system (Nzogela et al, 2020;Santos et al, 2012). P. zeae has been associated with significant yield reduction in sugarcane and rice crops (Namu et al, 2018;Nzogela et al, 2020;Singh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of this crops permits the reproduction and survival of the nematode species and might reduce the positive impact of the sugar cane/rice rotation system (Nzogela et al, 2020;Santos et al, 2012). P. zeae has been associated with significant yield reduction in sugarcane and rice crops (Namu et al, 2018;Nzogela et al, 2020;Singh et al, 2020). The genetic heterogeneity shown within the P. zeae populations from Costa Rica is consistent with previous reports (Carta et al, 2001;Mwamula et al, 2020;Subbotin et al, 2008), and supports that P. zeae could be a species complex.…”
Section: Discussionmentioning
confidence: 99%